(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
People are generally agreed to have more intelligence than any other animal. He works hard toimprove his lot in life by learning as much as he can via observation, experimentation, and other means.Throughout, he makes use of the data at his disposal by using various strategies. In this paper Discussthe Information Seeking Behaviour (ISB) and its Models.